Study Cracking Large Forgings of Low Carbon Steel Grade ST52, 3N Pressure Treatment; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Valuev D. V. Denis Viktorovich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen